Sense and Sensibility. - Austen, Jane, 1775-1817 (Open Road Media, 2016)
Torn between reason and passion, obligation and impulse, two sisters search for love in eighteenth-century England Although they are as close as sisters can be, Elinor and Marianne Dashwood could not be more different. Elinor is reasonable beyond her nineteen years; Marianne's feelings are as ungovernable as the wind. But both girls are about to learn how powerful and devastating true love can be. When Elinor meets the intelligent and mysterious Edward Ferrars, her commitment to self-control is tested for the first time. As her sister quietly endures the pain of heartbreak, Marianne longs for a romance of her own. She finds it in a chance encounter with John Willoughby, a dashing young rake who lives life as passionately as she does, and whose love could make her the happiest woman in England--or destroy her. A sparkling comedy of manners and an essential guide to navigating affairs of the heart, Jane Austen's first published novel is a timeless tale of love and loss. This ebook has been professionally proofread to ensure accuracy and readability on all devices.